Avant-garde dolls: Marie Vassilieff's portrait-dolls and the rise of a new aesthetic genre. (2019) - Richard, Julie
Abstract : This article studies the 'portrait-dolls' of the French-Russian artist Marie Vassilieff, active in Paris between the world wars. She made puppets that represented many famous artists of the École de Paris during the interwar period, many of which were presented in several exhibitions, many organized by her patron, the French fashion designer Paul Poiret (1879–1944). The article argues that Vassilieff created a new genre of portrait sculpture, which functioned as effigies, mementoes and decorative artefacts for the interwar Parisian avant-garde. Her portrait-dolls belong to the history of avant-garde puppets and marionettes, used in the performances of Sophie Taeuber-Arp and Hannah Höch among others, but also served a primitivist interest in the magical and uncanny character of figurative toys.